DC-link voltage balancing and control of qZ-source inverter fed induction motor drive - Thin Zar; Mai Kai Suan Tial; Tun Lin Naing (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Poor performance of the motor drive system is caused when the direct current-link (DC-link) capacitor voltages of the inverter are not sufficiently generated. This is mainly because of the various load torque changes and input voltage fluctuation. The qZ-source inverter operates with a fully shoot-through technique. This technique causes mismatching between the upper and lower DC-link capacitor voltages. Without capacitor voltage-balancing function, the desired DC-link capacitor voltages could not be provided or maintained when there are load and speed changes. A Sawtooth carrier-based simple boost triple-sixty-degree (TSD) pulse width modulation (PWM) technique is used to drive the qZ-source T-type inverter because this technique can give a more significant boost DC-link voltage than a traditional simple boost PWM technique. Proportional integral (PI) controller is applied for the DC-link voltage controller to achieve the fast response and less steady-state error. The simulation model was constructed for a 4 kW, 400 V, 1,400 rpm induction motor (IM) drive system used in rolling mill using MATLAB/Simulink with and without voltage balancing function. As a result, DC-link voltages of the qZ-source T-type inverter fed the induction motor drive system could be controlled using a capacitor voltage-balancing function and the output power of the motor from the simulation result is approximately equal to 4 kW.